Applying Implementation Science to Secure a Sustainable Supply of UNIMMAP MMS for National Antenatal Care Services in Indonesia. - Holik, Holis Abdul; Santika, Otte; Suwantika, Auliya; Atwater, John; de Lange, Jarno; Thaha, Abdul Razak; Achadi, Endang Laksminingsih; Nurlita, Hera; Rahmawati, Erni; Rimbawan; Ajello, Clayton (Nutrients, 2026)
Background: The United Nations International Multiple Micronutrient Antenatal Preparation of a multiple micronutrient supplement (UNIMMAP MMS or MMS) is replacing iron and folic acid supplementation (IFAS) in antenatal care (ANC) in low- and middle-income countries (LMICs). An investigation into determining how to secure a sustainable supply of MMS began in response to the Indonesian Ministry of Health (MOH)'s decision to introduce MMS into its national health services. Objective: We aimed to identify and test sustainable strategies for securing MMS supplies. Methods: A three-phase implementation science framework was applied to (1) foster an enabling environment for securing MMS supplies, (2) undertake implementation research (IR) to compare sourcing strategy options, and (3) plan and execute actions to scale MMS supply availability and distribution. The MOH assumed ownership of the initiative and guided policy, procurement, and program decisions. Results: (1) Landscaping resulted in recommendations that triggered supply-related policies, an accommodating regulatory framework, integration of MMS into key government support systems (i.e., budget, finance, procurement, and distribution), and identification of supply strategy options. (2) IR resulted in the selection of a local manufacturing and sourcing strategy for acquiring a sustainable supply of high-quality MMS product while retaining an option to import a limited supply of MMS during scaling. (3) A multi-year plan was developed to scale MMSs within ANC services. Conclusions: Applying implementation science provided an evidence-based framework with which to identify, establish, and test a sustainable strategy for securing MMS supplies and yielded insights useful for other countries introducing MMS into their national health systems.